Ex situ analysis of high-strength quenched and micro-alloyed steel during austenitising bending process: numerical simulation and experimental investigation - Lu, Yao; Xie, Haibo; Wang, Jun; Jia, Fanghui; Lin, Fei; Zhou, Cunlong; Xu, Jianzhong; Han, Jingtao; Jiang, Zhengyi (Springer, 2022)
This paper compares the microstructure and mechanical evolution in a high-strength quenched and micro-alloyed steel during the austenitising bending process. Simulation results indicated a new finding that the stress neutral layer (SNL) tends to move to the tension zone during straining. The hardness gradient detected from the centre to compression/tension zones was resulted from comprehensive factors: First of all, the location of SNL revealed a prominent impact on strength. Second, the dislocation accumulation would be responsible for the hardness gradient on the surfaces. In addition, the overall strength decrease during straining was mainly ascribed to integrated effects of dynamic recovery (DRV) and dynamic recrystallisation (DRX). Apart from that, overall smaller martensite packet size and coarser prior austenite grains resulted in the increased hardness value at a lower bending degree. Also, the high consistency between experimental and simulation results is instructive for the practical forming process of railway spring fasteners.
Keywords: High-strength quenched and micro-alloyed steel; Austenitising bending; Austenite reconstruction; Numerical simulation; Microstructure; Mechanical property